A Certain Class of Surfaces on Product Time Scales with Interpretations from Economics - Yilmaz, Emrah; Aydin, Muhittin Evren; Gulsen, Tuba (Univ Nis, Fac Sci Math, 2018)
In this study, we consider a graph surface associated to Cobb-Douglas production function in economics on product time scales. We classify this surface based on the flatness and minimality properties for several product time scales. Then, we interpret the obtained results from the perspective of production theory in economics. Therefore, we extend the known results in Euclidean geometry by considering time scale calculus.
Keywords: Time Scales; Surfaces; Delta derivatives; Production function